Decision Making style of Farm Women: a Critical Analysis - D. D. Suradkar,; V. D. Raut,; Supriya K. Deshpande,; D. D. Raut, (Journal of Agricultural Extension Management, 2014)
This study examines the constraints experienced by farm women while participating in decision making and the nature and extent of participation of farm women in decision making on farming. The constraints reported by the respondents are of varied types and intensity. The findings revealed that lack of time, lack of knowledge I information, poor economic status of the family, lack of adequate help and support, secondary status of women in family, and fear of failure were the important constraints faced by them. Majority of the farm women had medium level of participation in decision making on farming.